Investigating “head” and “heart” value traits of tertiary students studying in Cyprus - Zopiatis, Anastasios; Krambia-Kapardis, Maria (My University, 2008)
Abstract: Purpose – The purpose of this study is to investigate, for the first time in Cyprus, tertiary education students' personal values. In particular the study seeks to examine: the most important personal values for tertiary education students in two institutions in Cyprus; whether there are any differences between the individual's values as a function of variables such as gender, ethnic origin, year of study, type of academic discipline and religion; and whether there is a balance between “head” and “heart” traits amongst tertiary students. Design/methodology/approach – Following a comprehensive literature review the paper develops a quantitative questionnaire whereby tertiary students, currently pursuing accredited degrees in two tertiary institutions (one private and one public) were surveyed in order to identify their perceived level of importance from a list of 20 values with the utilization of a five-point Likert scale. A purposive (judgmental) sampling technique was utilized to select 1,000 cases from the population that would best meet the research purpose and address the study's research questions. The data were analyzed utilizing both descriptive and inferential statistics. Findings – Honesty, loyalty to family and friends, friendliness, self-confidence and world peace are ranked as the five most important personal values for college students in Cyprus. Surprisingly, traditionally important values such as patriotism and religion were ranked last by the respondents, both Cypriot and non-Cypriot. Originality/value – This would appear to be the first time that an investigation of this type has been undertaken in Cyprus.
Keywords: Students; Social values; Individual behaviour